2020
DOI: 10.1108/ijoes-12-2019-0190
|View full text |Cite
|
Sign up to set email alerts
|

Designing the model of factors affecting in the implementation of social and environmental accounting with the ISM approach

Abstract: Purpose Solely focusing on economic development and financial issues have led to insufficient attention to society and the environment, which has increased the injustice in this area. Accounting can aid to compensate for this harm and improve environmental issues. That is why social and environmental accounting (SEA) is rapidly growing and evolving. However, it has not been fully implemented yet. May be one cause for this issue is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 109 publications
(213 reference statements)
0
22
0
Order By: Relevance
“…So it can be argued that the EA mechanism is a strategy that has been used by the EPA to reduce corporate emissions to achieve a socially efficient level (Jiang and Tan, 2021; Oestreich, 2017). Voluntary EA in Ukraine aims to help businesses minimize their negative impacts on the environment and human health (Ruban and Rydén, 2018). EA can also be introduced to reduce water and fuel consumption (Rao et al , 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…So it can be argued that the EA mechanism is a strategy that has been used by the EPA to reduce corporate emissions to achieve a socially efficient level (Jiang and Tan, 2021; Oestreich, 2017). Voluntary EA in Ukraine aims to help businesses minimize their negative impacts on the environment and human health (Ruban and Rydén, 2018). EA can also be introduced to reduce water and fuel consumption (Rao et al , 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research result (Wu et al , 2020) showed that implementation of the EA has significantly improved the water quality. Thus, since the first application of EA in the US chemical and steel industry in the 1970s, EA has played an important role in resource management and pollution control of production systems (Ruban and Rydén, 2018). Waste reduction is also one of the effective factors on EA implementation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…This tool has a great impact on reducing greenhouse gas emissions. Governments can grant tax benefits to companies that are accepted in environmental audits (Oestreich, 2017; Muralikrishna et al , 2017; Bai et al , 2015; Ding and Pigram, 1996; Costantino et al , 2018; Ruban and Rydén, 2019; Sayyadi Tooranloo and Askari Shahamabad, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%